Modifications of auditory feedback and its effects on the voice of adult subjects: a scoping review - Alves, Moisés do Carmo; Mancini, Patrícia Cotta; Teixeira, Leticia Caldas (CoDAS (São Paulo), 2024)
ABSTRACT Introduction The auditory perception of voice and its production involve auditory feedback, kinesthetic cues and the feedforward system that produce different effects for the voice. The Lombard, Sidetone and Pitch-Shift-Reflex effects are the most studied. The mapping of scientific experiments on changes in auditory feedback for voice motor control makes it possible to examine the existing literature on the phenomenon and may contribute to voice training or therapies. Purpose To map experiments and research results with manipulation of auditory feedback for voice motor control in adults. Method Scope review following the Checklist Preferred Reporting Items for Systematic reviews and Meta-Analyses extension (PRISMA-ScR) to answer the question: “What are the investigation methods and main research findings on the manipulation of auditory feedback in voice self-monitoring of adults?”. The search protocol was based on the Population, Concept, and Context (PCC) mnemonic strategy, in which the population is adult individuals, the concept is the manipulation of auditory feedback and the context is on motor voice control. Articles were searched in the databases: BVS/Virtual Health Library, MEDLINE/Medical Literature Analysis and Retrieval System online, COCHRANE, CINAHL/Cumulative Index to Nursing and Allied Health Literature, SCOPUS and WEB OF SCIENCE. Results 60 articles were found, 19 on the Lombard Effect, 25 on the Pitch-shift-reflex effect, 12 on the Sidetone effect and four on the Sidetone/Lombard effect. The studies are in agreement that the insertion of a noise that masks the auditory feedback causes an increase in the individual's speech intensity and that the amplification of the auditory feedback promotes the reduction of the sound pressure level in the voice production. A reflex response to the change in pitch is observed in the auditory feedback, however, with particular characteristics in each study. Conclusion The material and method of the experiments are different, there are no standardizations in the tasks, the samples are varied and often reduced. The methodological diversity makes it difficult to generalize the results. The main findings of research on auditory feedback on voice motor control confirm that in the suppression of auditory feedback, the individual tends to increase the intensity of the voice. In auditory feedback amplification, the individual decreases the intensity and has greater control over the fundamental frequency, and in frequency manipulations, the individual tends to correct the manipulation. The few studies with dysphonic individuals show that they behave differently from non-dysphonic individuals. RESUMO Introdução A percepção auditiva da voz e sua produção envolvem o feedback auditivo, as pistas cinestésicas e o sistema de feedforward, os quais produzem efeitos distintos para a voz. Os efeitos Lombard, Sidetone e o Pitch-Shift-Reflex são os mais estudados. O mapeamento de experimentos científicos sobre as modificações do feedback auditivo para o controle motor da voz possibilita examinar a literatura existente sobre o fenômeno e pode contribuir para o treinamento ou terapias da voz. Objetivo Mapear os experimentos e resultados das pesquisas com manipulação do feedback auditivo para o controle motor da voz de indivíduos adultos. Método Revisão de escopo seguindo o Checklist Preferred Reporting Items for Systematic reviews and Meta-Analyses extension (PRISMA-ScR) para responder à pergunta: “Quais os métodos de investigação e principais achados das pesquisas sobre a manipulação do feedback auditivo no automonitoramento da voz de indivíduos adultos?”. O protocolo de busca foi baseado na estratégia mnemônica População, Conceito e Contexto (PCC). A população são os indivíduos adultos; o conceito é a manipulação do feedback auditivo e o contexto é o controle motor da voz. Os artigos foram pesquisados nas bases de dados: BVS/ Biblioteca Virtual em Saúde, MEDLINE/Medical Literature Analysis and Retrieval Sistem on-line, COCHRANE, CINAHL/Cumulative Index to Nursing and Allied Health Literature, SCOPUS e WEB OF SCIENCE. Resultados Foram encontrados 60 artigos, sendo 19 da temática do Efeito Lombard, 25 do efeito Pitch-shift-reflex, 12 do efeito Sidetone e quatro sobre o efeito Sidetone/Lombard. Os estudos são concordantes que a inserção de um ruído que mascara o feedback auditivo provoca um aumento na intensidade de fala do indivíduo e que a amplificação do feedback auditivo promove a redução do nível de pressão sonora na produção da voz. Observa-se uma resposta reflexa à mudança de tom no feedback auditivo, porém, com características individuais em cada estudo. Conclusão O material e método dos experimentos são distintos, não há padronizações nas tarefas, as amostras são variadas, muitas vezes reduzidas. A diversidade metodológica dificulta a generalização dos resultados. Os principais achados das pesquisas a respeito o feedback auditivo sobre o controle motor da voz confirmam que, na supressão do feedback auditivo, o indivíduo tende a aumentar a intensidade da voz. Na amplificação do feedback auditivo, o indivíduo diminui a intensidade e tem maior controle sobre a frequência fundamental e, nas manipulações da frequência, o indivíduo tende a corrigir a manipulação. Os poucos estudos com sujeitos disfônicos mostram que eles se comportam diferentemente dos não disfônicos.